Towards a Decolonized and Africanized School History Curriculum in post apartheid South Africa - Maluleka, Paul (University of the Witwatersrand, Johannesburg, 2023)
This study explores and discusses ways in which the School History Curriculum (SHC) in South Africa was designed by colonialists to depict their history favourably and how this continues to be the case after independence. The study also investigates ways in which the SHC could be decolonized and Africanized, especially where knowledge building is a concern. This is done both conceptually and empirically. Conceptually, a critical decolonial conceptual framework strengthened with Bernstein’s Code Theory and Pedagogic Device, Maton’s Epistemic-Pedagogic Device, and Legitimation Code Theory’s Autonomy dimension were employed. Firstly, to highlight how the legacy of colonialism, apartheid, coloniality, and their monolithic epistemic nature, and to some extent, their alienating pedagogic and assessment practices, continue to underpin the SHC in post-apartheid South Africa. Secondly, to explore conceptual ways in which decoloniality could be applied in curriculum knowledge building and its structures in cumulative and principled ways. This was done to counter much of the knowledge blindness that characterize sociology of education including many of the calls for decolonization and Africanization. In turn, this was meant to reposition scholarship on decolonization and Africanization to also be vested in a sociological approach to knowledge and curriculum that is vested in investigating the relations within knowledge and curriculum and their intrinsic structures. A qualitative research approach was adopted, and semi-structured interviews were used as methods of generating empirical data, with descriptive and interpretive elements of data analysis used to engage the data. Empirically, four in-service history educators from Gauteng and Limpopo Provinces were purposefully and conveniently selected. The purpose of interviewing in-service history educators was to gain insights into how they thought of the current SHC. Whether, according to them, calls to decolonize and Africanize the SHC were imperative and justified, and how they could be carried out. Both the conceptual and empirical findings reveal that there is a need to decolonize and Africanize SHC in post-apartheid South Africa given that its knowledge base is still characterized by the legacy of colonialism, apartheid, and coloniality. To achieve this, both the conceptual and empirical findings pointed out the need to reimagine and construct epistemologies, ontologies and methodologies that not only move beyond universal explanations of the world; but embrace trans-modernist and pluriversal explanations of the world. These are informed and shaped by time and the place, perspective, orientation, and situatedness of their authors. Secondly, the findings of the study revealed how historical knowledge is both dialectically and intersectionally produced, recontextualized and reproduced in the three fields of practice. Interrogating critically who are the knowers that are legitimated and de-legitimated in all these processes, can enable us to better understand the colonizing gaze that continues to characterize the SHC. It can also allow us to better understand how these fields of practice can also be seen as spaces where de-legitimated knowledge and knowers are recentred and where decolonization and Africanization can happen. This would see the continued marginalization of indigenous knowledge systems, traditions, and cultural practices in the SHC at the altar of Eurocentric methods being disrupted. Thirdly, the findings also pointed out that presently CAPS SHC does not have a settled African philosophy (of education): it is torn between two worlds, i.e., the universal and the particular. In a strict education for Africanization sense, the SHC in post-apartheid South African schools should be perceived first and foremost as a professional philosophical project that African philosophers in higher education devote their time and energy to. Second, a sage project that oMakhulu’s as part of the broader school communities help in-service history educators and their learners through oral history and research projects to address problems and deal with issues facing locals. Last, but not least, it should be perceived as a hermeneutic project that brings philosophy down from the sky, i.e., helps both in-service educators and their learners to make practical sense of deep philosophical issues in post-apartheid South African schools.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in History Education, to the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Africanization; African philosophy; CAPS; Curriculum knowledge; Decoloniality; Decolonization; Epistemic-Pedagogic Device; Fallism; Fees Must Fall; School History; South Africa; UCTD; SDG-4: Quality education